Buckling of chiral elastic rings spanned by fluid films - Hoang Minh Tuan; Nguyen Thi Lan; Tran Minh Tuyen (Vietnam Journal of Mechanics)
We use variational method to examine buckling of chiral elastic rings spanned by fluid films. We find that the critical surface tension of the fluid film at which buckling occurs depends on the degree of chirality, regardless whether the ring possesses left-handed chirality or right-handed chirality. Additionally, the chirality always has a destabilizing effect on buckling, yielding to buckle at a critical surface tension smaller than that of the achiral elastic rings. The destabilizing effect of chirality, however, can be reduced by increasing the twisting rigidity to bending rigidity of filaments (twist-to-bend ratio).